(untitled) (Revista de Psicología, 2019)
By the end of the ’60, the model of heath of that time started to change (Prada, 2005), deepening itself in the healthful aspects of the human being, in the strengths, in its virtues and how these aspects affects in the people life and in the societies in which they live (Cuadra & Florenzano, 2003). Considering the importance of the well-being as far as the valuation of the positive operation and the development of the people, an empirical study was made to evaluate and to compare the levels of Psychological Well-being (Ryff, 1989) and Social welfare (Keyes, 1998) in university students. According to the obtained results, the young people present/display high levels of psychological and social well-being, although differences in relation to sociodemográficas variables exist.